Revealing the Electron-Spin Fluctuation Coupling by Photoemission in CaKFe_{4}As_{4} - Peng Li; Yuzhe Wang; Yabin Liu; Jianghao Yao; Zhisheng Zhao; Zhengtai Liu; Dawei Shen; Huiqian Luo; Guanghan Cao; Juan Jiang; Donglai Feng (Physical Review X)
Electron-boson coupling in unconventional superconductors is one of the key parameters in understanding the superconducting pairing symmetry. Here, we report definitive photoemission evidence of electron-spin fluctuation coupling in the iron-based superconductor CaKFe_{4}As_{4}, obtained via high-resolution ARPES. Our study identifies a distinct kink structure on the α band, observable only in the superconducting phase and closely linked with the superconductivity, indicative of strong electron-boson interactions. Notably, this kink structure corresponds to two distinct bosonic modes at 11 meV and 13 meV, aligning with spin resonance modes previously observed in inelastic neutron-scattering experiments. This alignment underscores the significant role of antiferromagnetic fluctuations in the pairing mechanism of this superconductor. Furthermore, the unique momentum-dependent and orbital-selective properties of the coupling revealed by ARPES provide profound insights into the pairing symmetry, suggesting predominantly s_{±}-wave pairing facilitated by spin fluctuations. Our findings not only highlight the pivotal role of spin resonance in the superconductivity of CaKFe_{4}As_{4} but also enhance our understanding of the electron-spin fluctuation interactions in unconventional superconductors.